“Telling” insights from experience: Establishing resonance with readers, theory, and participants - Chanock, Kate (Journal of Academic Language and Learning, 2014)
This special issue of the JALL was conceived as a bridge between theory and practice. This is a two-lane bridge: for while theory informs practice, the converse is also true, or ought to be. It can be difficult, however, to engage in dialogue with theory, and not only because our work leaves little time for reflection or writing. It is also, I think, because we lack a genre for this purpose; and my aim in this piece is to encourage more theoretically inflected narratives from the “ground” of practice. Research is normally planned, “systematic and sustained inquiry,” (Stenhouse, 1981, p. 113), but there are occasionally contributions to the scholarship of learning and teaching that are not the products of designed research, but by-products of teaching. These arise out of moments in practice when something happens that resonates with discussions in our field, and seems to show something about teaching/learning that is worth communicating with colleagues. If we wish to share these “telling” cases with our community of practice, we must consider: • how can we bring such stories into the scholarly conversation, and • what problems must be beware of, in attempting this? This article explores two kinds of resonance that enable “telling” stories (Mitchell, 1984) to be told: resonance with readers, and resonance with theory. At the same time, it acknowledges the range of ways in which such accounts may be felt to lack validity, and argues for collaboration with the students whose stories we may wish to tell, in order to ensure what Maxwell (1992) calls “interpretive validity”.